2018
DOI: 10.1158/1535-7163.mct-17-0868
|View full text |Cite
|
Sign up to set email alerts
|

PIM Kinases Are a Potential Prognostic Biomarker and Therapeutic Target in Neuroblastoma

Abstract: The majority of high-risk neuroblastoma patients are refractory to, or relapse on, current treatment regimens, resulting in 5-year survival rates of less than 50%. This emphasizes the urgent need to identify novel therapeutic targets. Here, we report that high kinase expression is correlated with poor overall survival. Treatment of neuroblastoma cell lines with the pan-PIM inhibitors AZD1208 or PIM-447 suppressed proliferation through inhibition of mTOR signaling. In a panel of neuroblastoma cell lines, we obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…These findings are consistent with previous reports on PI3K inhibition in neuroblastoma (Chesler et al, 2006;Johnsen et al, 2008;Chanthery et al, 2012;Cage et al, 2015). Similarly, PIM inhibition has previously been suggested as a therapeutic option in MYC/MYCN-associated tumor types (Kirschner et al, 2014;Horiuchi et al, 2016;Brunen et al, 2018). Our results of combined PIM/PI3K inhibition effects in neuroblastoma are in line with findings from other tumor types including breast cancer (Le et al, 2016) and glioblastoma (Iqbal et al, 2016).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with previous reports on PI3K inhibition in neuroblastoma (Chesler et al, 2006;Johnsen et al, 2008;Chanthery et al, 2012;Cage et al, 2015). Similarly, PIM inhibition has previously been suggested as a therapeutic option in MYC/MYCN-associated tumor types (Kirschner et al, 2014;Horiuchi et al, 2016;Brunen et al, 2018). Our results of combined PIM/PI3K inhibition effects in neuroblastoma are in line with findings from other tumor types including breast cancer (Le et al, 2016) and glioblastoma (Iqbal et al, 2016).…”
supporting
confidence: 93%
“…Activation of the PIM kinases is thought to be an important PI3K inhibitor resistance mechanism (Le et al , ). While little is known about the role of PIM kinases in neuroblastoma, a recent report suggested that PIMs might serve as prognostic biomarkers and putative treatment targets in this tumor type (Brunen et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of MET has previously been shown to confer resistance to the ALK inhibitor alectinib in NSCLC 31 , and resistance can be overcome with crizotinib, a potent inhibitor of MET 32 . Given substantial evidence in the literature that PIM1 mediates resistance to standard chemotherapy [33][34][35] as well as molecularly targeted agents 36,37 , that high expression of PIM1 is a poor prognostic indicator in multiple cancers [38][39][40] , and that recently Brunen et al 41 . identified PIM kinases as potential therapeutic targets in NF1 wild-type NB, this gene was explored further.…”
Section: Resultsmentioning
confidence: 99%
“…Proviral integration site for Moloney murine leukemia virus-1 (PIM-1) is a serine/threonine kinase, involved in cell cycle progression, cell growth, cell survival and therapy resistance. PIM-1 is activated in various types of cancer, amongst which prostate [14][15][16] , colorectal [15,[17][18][19] , triple negative breast cancer (TNBC) [20,21] , hematologic malignancies [22][23][24] , neuroblastoma [25] and lung cancer [26] . For this reason, PIM kinases could provide a common target for the treatment of diverse malignancies.…”
Section: Introductionmentioning
confidence: 99%